Isothermal growth kinetics of CdxHg₁₋xTe LPE layers - Moskvin, P.P.; Khodakovsky, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
Within the diffusion-limited growth model, the kinetic analysis of the LPE process for CdxHg₁₋xTe solid solutions is carried out. It is assumed that a phase equilibrium exists on the interface, and the concentrations of components are connected by the equations of phase equilibria in the frame of the model of polyassociated solutions. These equations serve as the boundary conditions in solving the diffusion mass transfer problem. The developed thermodynamic model of growth allowed us to achieve the precision description of solid solutions, in particular to predict the regimes of the growth of layers with a given composition in the Cd-Hg-Te system.